2000
DOI: 10.4315/0362-028x-63.1.126
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Membrane Filtration Rates and Hydrophobic Grid Membrane Filter Coliform and Escherichia coli Counts in Food Suspensions Using Paddle-Type and Pulsifier Sample Preparation Procedures

Abstract: Food suspensions prepared by Pulsifier contained less debris and filtered 1.3x to 12x faster through hydrophobic grid membrane filters (HGMFs) than those prepared by Stomacher 400. Coliform and Escherichia coli counts made by an HGMF method yielded 84 and 36 paired samples, respectively, positive by both suspending methods. Overall counts of pulsificates and stomachates did not differ significantly for either analysis, though coliform counts by Pulsifier were significantly higher in mushrooms and significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…New laboratories that work on the detection of viruses or bacteria in foods and environmental samples may thus choose to invest in a pulsifier over a stomacher, but there are neither data in the literature on the use of a pulsifier for homogenization of fecal material nor data on the recovery of F-RNA coliphages from pulsified suspensions. There was no significant difference between fecal samples homogenized with a stomacher and those homogenized with a pulsifier, and the ratios of results with the pulsifier to those with the stomacher were comparable to the findings of others (5,13,23,30). Because fecal material has a loose consistency, the amount of debris generated with a pulsifier is expected to be similar to that obtained with a stomacher, and therefore there is no advantage for downstream PCRs by use of a pulsifier as opposed to a stomacher for homogenizing fecal material.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…New laboratories that work on the detection of viruses or bacteria in foods and environmental samples may thus choose to invest in a pulsifier over a stomacher, but there are neither data in the literature on the use of a pulsifier for homogenization of fecal material nor data on the recovery of F-RNA coliphages from pulsified suspensions. There was no significant difference between fecal samples homogenized with a stomacher and those homogenized with a pulsifier, and the ratios of results with the pulsifier to those with the stomacher were comparable to the findings of others (5,13,23,30). Because fecal material has a loose consistency, the amount of debris generated with a pulsifier is expected to be similar to that obtained with a stomacher, and therefore there is no advantage for downstream PCRs by use of a pulsifier as opposed to a stomacher for homogenizing fecal material.…”
Section: Discussionsupporting
confidence: 83%
“…A pulsifier, which homogenizes samples by creating shock waves through high-speed beating action with an oscillating ring, is a recent alternative to a stomacher, which uses crushing action to homogenate samples (5). The pulsifier has been tested on food samples, and the recovery of microorganisms from foods homogenized with a pulsifier is equivalent to that from foods homogenized with a stomacher (5,13,23,30). With the exception of foods that have a low level of cohesiveness, suspensions that are homogenized with a pulsifier contain less debris than that obtained with a stomacher, which is an advantage for downstream reactions such as PCR.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our data, Cook et al (5) reported that pummeling and pulsifying were more efficient than shaking or rolling, and no significant difference between pummeling and pulsifying was found for recovery of Cryptosporidium parvum from lettuce and raspberries. Sharpe et al (13) found that the superiority of pulsifying over pummeling for recovery of microorganisms from foods was not clear. However, pulsifying is less destructive than pummeling, producing smaller amounts of debris, and it is superior to pummeling for molecular biological analysis and immunoassays such as PCR, ATP bioluminescence, and immunomagnetic beads, which are easily affected by the condition of tissue extracts (7).…”
Section: Discussionmentioning
confidence: 99%
“…As PBS is used frequently as a wetting agent and diluent in food microbiology and virology and it does not contain compounds that interfere with or are inhibitory for downstream molecular detection assays, alternate methods to dislodge MS2 from cellulose acetate sponges in the presence of PBS were explored. While several studies have demonstrated that homogenization with a pulsifier is equivalent to a stomacher (Fung et al, 1998;Kang et al, 2001;Sharpe et al, 2000;Wu et al, 2003) and sonication is used to recover F-RNA coliphages from membrane filters and has the potential to increase the recovery of viruses from centrifugal ultrafiltration devices Méndez et al, 2004), stomaching alone or in combination with sonication did not improve the recovery of MS2 from sponges when PBS was used as an eluant.…”
Section: Discussionmentioning
confidence: 99%